ANALISIS PENDAPATAN USAHATANI PADI SAWAH DI DESA KOLE SAWANGAN KECAMATAN MALIMBONG BALEPE KABUPATEN TANA TORAJA (Income Analysis of Rice Farming Business in Kole Sawangan Village, Malimbong Balepe Sub District, Tana Toraja Regency) - Melsiana Tangaran; Martha M. Sendow; Theodora M. Katiandagho (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
Tho objective of this research is to analyze the amount of income from lowland rice farming in Kole Sawangan Village, Malimbong Balepe Sub District, Tana Toraja Regency. The type of data used in this study is primary data obtained directly from interviews and through questionnaires distributed to respondent farmers and secondary data is data obtained from other sources that serve as supporting data, such as from books or research results. that has been done and data from the Department of Agriculture and related agencies in Tana Toraja Regency. The number of samples in this study amounted to 27 people with data collection techniques using Simple Random Sampling technique. Analysis of the data used is descriptive data analysis. The results of this research indicated that the average income of rice farmers in one growing season in Kole Sawangan Village, Malimbong Balepe SubDistrict, Tana Toraja Regency is Rp.2,362,592/0.25 Ha and the average income per hectare is Rp.9,312,408.